Säsongsvis avverkning : det operativa traktvalets påverkan på den säsongsmässiga uthålligheten i ett bolagsdistrikts traktbank - Renström, Johan (SLU/Dept. of Forest Resource Management, 2008)
Due to soft grounds in combination with seasonal variation in soil humidity, there is a lack of stands that are possible to cut during spring and autumn in some geographical regions. For Holmen Skog this sometimes means that a large proportion of the contracted private forest is cut during the winter when the ground is frozen. One consequence of this is that the proportion of winter stands in the stand bank of own forest increases while spring and autumn stands becomes a scarcity. This in combination with milder winters, especially when there is a long period of reduced bearing capacity in spring or autumn, means that the situation rapidly can become critical.